1980
DOI: 10.1002/jpln.19801430403
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of zinc deficiency in cotton

Abstract: The diagnosis of Zn deficiency in cotton by means of total analysis or the appearance of deficiency symptoms is unsatisfactory. In order to obtain a better understanding of the development of Zn deficiency symptoms in relation to Zn content cotton plants were cultivated in waterculture under reproducible environmental conditions and Zn deficiency induced by different means.It was observed that deficiency symptoms developed equally, regardless of the inducing factors such as low Zn in the nutrient solution, hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
1

Year Published

1982
1982
2019
2019

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 18 publications
1
4
1
Order By: Relevance
“…This finding indicate that Zn content per shoot, but not Zn concentration per unit of shoot dry weight, is a reliable criterion for assessing genotypes for their tolerance to Zn deficiency, confirming the previous results with genotypes of different cereal species (Graham and Rengel, 1993;Rengel and Graham, 1995b;Cakmak et al, 1997bCakmak et al, , 1998. In most cases, tissue Zn concentration was not considered as a suitable measure for determination of the Zn nutritional status of plants (Ghoneim and Bussler, 1980;Cakmak and Marschner, 1987). Higher Zn content of the Zn-efficient genotypes (Tables 2 and 4) might be a reflection of greater capacity of these genotypes to absorb Zn from soil.…”
Section: Discussionsupporting
confidence: 86%
“…This finding indicate that Zn content per shoot, but not Zn concentration per unit of shoot dry weight, is a reliable criterion for assessing genotypes for their tolerance to Zn deficiency, confirming the previous results with genotypes of different cereal species (Graham and Rengel, 1993;Rengel and Graham, 1995b;Cakmak et al, 1997bCakmak et al, , 1998. In most cases, tissue Zn concentration was not considered as a suitable measure for determination of the Zn nutritional status of plants (Ghoneim and Bussler, 1980;Cakmak and Marschner, 1987). Higher Zn content of the Zn-efficient genotypes (Tables 2 and 4) might be a reflection of greater capacity of these genotypes to absorb Zn from soil.…”
Section: Discussionsupporting
confidence: 86%
“…There is some evidence that the water-soluble Zn fraction may be a better predictor of deficiency than total leaf Zn (e.g. Cakmak and Marschner, 1987), but contrary findings have also been reported (Ghoneim and Bussler, 1980). In our experiments, soluble Zn did not follow consistent trends and, except in stem tissue, was always considerably higher than the 5 to 7 mg kg ~ reported to be the minimum for norreal growth (Cakmak and Marschner, 1987).…”
Section: Zinc-phosphorus Interactions In Tomato 173contrasting
confidence: 52%
“…Rahimi and Bussler (1979) and Ghoneim and Bussler (1980) studied Zn responses of a number of crop species, and concluded that 'latent deficiencies' could occur at leaf Zn concentrations as high as 35mgkg ~. There is some evidence that the water-soluble Zn fraction may be a better predictor of deficiency than total leaf Zn (e.g.…”
Section: Zinc-phosphorus Interactions In Tomato 173mentioning
confidence: 99%
“…Plant analysis has been shown to be an effective method for diagnosis of Zn deficiency. The use of composite plant samples for diagnosis of Zn deficiency was found to be unsuitable or inferior to young mature leaves in soybean (Ohki, 1977), maize (Weir and Miiham, 1978), cotton (Ghoneim and Bussler 1980), tropical legumes (Andrew et al, 1918), subterranean clover (Reuter et al, 1982), and navy bean (Armour et al, 1990).…”
Section: Introductionmentioning
confidence: 99%